Emotional intelligence and the experiencing and valuing of the “feminine self” - Martowska, Katarzyna; Wrocławska-Warchala, Emilia (Studia Psychologica: Theoria et praxis, 2010)
The starting point of this research is the presumption that the emotional intelligence is an important factor in shaping the way of selfexperiencing and selfvaluing. In this research the authors have focused on the special area of the self, defined as the “feminine self”, connected with the experien cing and valuing oneself as a woman. The participants were young adult women. To measure the emotional intelligence, the selfdescription Emotional Intelligence Scalę was used (INTE, by N.S. Shutte et al, in Polish adaptation by Aleksandra Jaworowska and Anna Matczak). The modification of the SelfConfrontation Method by Hubert J.M. Hermans, adapted to the research purpose, helped to discem the varieties of experiencing and valuing oneself as a woman. Firstly, the participants answered to the open ąuestions conceming the way of perceiving and experiencing their femininity by themselves and by others. Then, they described the ąuality and intensity of the feelings connected with experientives was gathered, which subseąuently were quantitatively and qualitatively analyzed (e.g. following indices of experiencing feminine self were calcula ted: the intensity of positive and negative feelings, the intensity of feelings connected with “strengthening the self ’ and “strengthening the relation with others” motives). In the description of the research results presented in the article we have focused on the femininity dimensions differentiated in the process of analyzing the narratives, as well as on the interpretation of the connection between the emotional intelligence and these dimensions.